2020
DOI: 10.1177/2192568220980441
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between the Rotator Cuff Status and the Severity and Recovery of Weakness in the Shoulder Abductor Strength in a Case of Proximal Type Cervical Spondylotic Amyotrophy

Abstract: Study Design: Case series study. Objective: We aimed to clarify the prevalence of rotator cuff tear (RCT), and the association between RCT and the severity and prognosis in patients with proximal type cervical spondylotic amyotrophy (CSA). Methods: We retrospectively analyzed 35 proximal type CSA patients who were treated conservatively. The following data was collected: age, rotator cuff status on MRI, manual muscle test (MMT) score of shoulder abductor and biceps brachii muscles both at the first visit and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…The manual muscle test has previously been proven to be a reliable and valid examination tool for clinical applications [24]. Consistent with our approach, Sho Ishiwata also used the manual muscle test in one study to measure the SAS [18]. The nomogram clearly showed that a SAS grade 0-2 had a strong predictive ability: the weight was high, and the corresponding points were between 60 and 70.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The manual muscle test has previously been proven to be a reliable and valid examination tool for clinical applications [24]. Consistent with our approach, Sho Ishiwata also used the manual muscle test in one study to measure the SAS [18]. The nomogram clearly showed that a SAS grade 0-2 had a strong predictive ability: the weight was high, and the corresponding points were between 60 and 70.…”
Section: Discussionsupporting
confidence: 65%
“…Previous studies have shown that a grade of ASIA A and an injury level above C4 are the most common predictors of tracheostomy [16,17]. The shoulder abduction is accomplished by the deltoid in conjunction with the supraspinatus [18]. The deltoid is innervated by the axillary nerve, and the supraspinatus is innervated by the suprascapular nerve.…”
Section: Introductionmentioning
confidence: 99%